Time-resolved step-scan Fourier transform infrared investigation of heme-copper oxidases: implications for O 2 input and H 2O/H + output channels - Koutsoupakis, Constantinos; Pinakoulaki, Eftychia; Stavrakis, Stavros; Daskalakis, Vangelis; Varotsis, Constantinos (My University, 2004)
We have applied FTIR and time-resolved step-scan Fourier transform infrared (TRS 2-FTIR) spectroscopy to investigate the dynamics of the heme-Cu B binuclear center and the protein dynamics of mammalian aa 3, Pseudomonas stutzeri cbb 3, and caa 3 and ba 3from Thermus thermophilus cytochrome oxidases. The implications of these results with respect to (1) the molecular motions that are general to the photodynamics of the binuclear center in heme-copper oxidases, and (2) the proton pathways located in the ring A propionate of heme a 3-Asp372- H 2O site that is conserved among all structurally known oxidases are discussed
Keywords: Fourier transform infrared spectroscopy; Heme; Copper; Mammals; Pseudomonas; Oxygen; Molecular dynamics